2020
DOI: 10.1093/elt/ccaa044
|View full text |Cite
|
Sign up to set email alerts
|

Triggering effect of CLIL practice on English as a lingua franca awareness

Abstract: The present study explores whether/how CLIL practice at primary English language classrooms raises English language teachers’ awareness towards their language use from an English as a lingua franca (ELF)-aware perspective. English language teachers in a CLIL program completed a survey about their classroom practice and their opinions about their English language use in the classroom. They also shared their lesson plans to showcase their everyday teaching. The findings revealed that although CLIL practice prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The research reported the description of detailed specific decision-making process with regards to the evaluation of CLIL practice in Italian English language teaching context. More recently, (Yalçın, Bayyurt, and Alahdab 2020) investigated how CLIL practice at English classrooms enhanced the teachers' awareness toward their use of language as seen from English as a lingua franca perspective. Through a survey about the teachers' CLIL practices in language classrooms, the results showed that the teachers encountered several challenges in implementing CLIL in their classrooms.…”
Section: A Introductionmentioning
confidence: 99%
“…The research reported the description of detailed specific decision-making process with regards to the evaluation of CLIL practice in Italian English language teaching context. More recently, (Yalçın, Bayyurt, and Alahdab 2020) investigated how CLIL practice at English classrooms enhanced the teachers' awareness toward their use of language as seen from English as a lingua franca perspective. Through a survey about the teachers' CLIL practices in language classrooms, the results showed that the teachers encountered several challenges in implementing CLIL in their classrooms.…”
Section: A Introductionmentioning
confidence: 99%
“…In fact, the nationwide adoption of the CLIL approach by Italian English language teachers, particularly in primary and upper secondary schools since 2012 has helped them achieve meaningful interaction in or outside class and shift their focus away from learners' mistakes (Hüttner, 2018). Like in ELF-aware classrooms, the emphasis on effective and meaningful communication, contextualization, the avoidance of native speakeroriented pedagogies and the empowerment of learners to become competent users of English are the main features of CLIL classrooms (See Yalçın, Bayyurt, & Alahdab, 2020). Hence CLIL practices in Italy could be considered "complimentary" to ELFaware ones (Yalçın et al, 2020, p. 8).…”
Section: Italymentioning
confidence: 99%
“…Just like in ELF-aware practices, she reported that in CLIL practices the focus was on using English and creating a motivating and an engaging environment for learners to start using English, to enable them to become confident users of English (Kordia, 2018;Sifakis & Bayyurt, 2018). Also, the use of English as the medium of instruction in the CLIL lessons enabled her to focus on effective communication strategies (Yalçın et al, 2020). Just as Bayyurt and Sifakis (2015b) reported in their ELFTEd project, P12 pointed out that the emphasis on content in her CLIL classroom enabled her to use English for authentic purposes.…”
Section: Meaning Scheme 2: Teaching and Learning English From The Elf And We Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations